Sodium Bicarbonate in Different Critically Ill Conditions: From Physiology to Clinical Practice. (15th March 2021) - Coppola, Silvia; Caccioppola, Alessio; Froio, Sara; Chiumello, Davide
Abstract : Intravenous sodium bicarbonate is commonly used in several critically ill conditions for the management of acute acidemia independently of the etiology, and for the prevention of acute kidney injury, although this is still controversial from a physiologic point of view.